Student’s Misbehavior in Online Learning at SMK Taman Siswa Padang - Suryandi, An Putri Rima; Sevrika, Hevriani; Autila, Rani (Jurnal Pendidikan Tambusai, 2021)
The problem in this study is why students are not disciplined in online learning at SMK Taman Siswa Padang. Starting from the problems above, this study aims to analyze the reasons students do not discipline in online learning. This type of research is qualitative; the participants of this research are students of class XII TKR (Light Vehicle Engineering) at SMK Taman Siswa Padang in the academic year 2021/2022. The instruments used in this study were Questionnaires and Interviews. To test the validity of the data, the researcher combined the results of the Questionnaire and Interview. Next in doing the analysis. The results showed that students who were not disciplined in online learning at SMK Taman Siswa Padang were: 1. did not like online learning 2. did not care about online learning 3. there was no student interest in online learning 4. there was no student motivation in online learning.